Cleavage-Independent HIV-1 Trimers From CHO Cell Lines Elicit Robust Autologous Tier 2 Neutralizing Antibodies - Bale, Shridhar; Martiné, Alexandra; Wilson, Richard; Behrens, Anna-Janina; Le Fourn, Valérie; de Val, Natalia; Sharma, Shailendra K.; Tran, Karen; Torres, Jonathan L.; Girod, Pierre-Alain; Ward, Andrew B.; Crispin, Max; et al. (Frontiers in Immunology, 2018)
Native flexibly linked (NFL) HIV-1 envelope glycoprotein (Env) trimers are cleavage-independent and display a native-like, well-folded conformation that preferentially displays broadly neutralizing determinants. The NFL platform simplifies large-scale production of Env by eliminating the need to co-transfect the precursor-cleaving protease, furin that is required by the cleavage-dependent SOSIP trimers. Here, we report the development of a CHO-M cell line that expressed BG505 NFL trimers at a high level of homogeneity and yields of 1.8 g/L. BG505 NFL trimers purified by single-step lectin-affinity chromatography displayed a native-like closed structure, efficient recognition by trimer-preferring bNAbs, no recognition by non-neutralizing CD4 binding site-directed and V3-directed antibodies, long term stability and proper N-glycan processing. Following negative-selection purification, formulation in ISOMATRIX adjuvant and inoculation into rabbits, the trimers rapidly elicited potent autologous tier 2 neutralizing antibodies. These antibodies targeted the N-glycan “hole” naturally present on the BG505 Env proximal to residues at 230, 241 and 289 positions. The BG505 NFL trimers that did not expose V3 in vitro, elicited low-to-no tier 1 virus neutralization in vivo, indicating that they remained intact during the immunization process. Additionally, BG505 NFL and BG505 SOSIP trimers expressed from 293F cells, when formulated in Adjuplex adjuvant, elicited equivalent BG505 tier 2 autologous neutralizing titers. These titers were lower in potency when compared to the titers elicited by CHO-M cell derived trimers. In addition, increased neutralization of tier 1 viruses was detected. Taken together, these data indicate that both adjuvant and cell-type expression can affect the elicitation of tier 2 and tier 1 neutralizing responses in vivo.